Fêlures. Nouveaux regards sur les frontières dans les Amériques (xvie-xxie siècle) - Soizic Croguennec; Silvia Lopes da Silva Macedo (Mélanges de la Casa de Velázquez)
So-called “peripheral” regions, remote from the centers of political and economic power, borderlands are regularly perceived through the prism of backwardness in relation to a dominant and rewarding social, economic, and cultural model. To question and shed light on these dynamics, the notion of “crack” taken in all its polysemy appears particularly stimulating to reconsider many facets of borderlands. For this dossier at the crossroads of history, geography, and anthropology, the choice was made to present case studies rooted in well-defined contexts – the figures of failure, the setbacks of conquest, imperial or national bankruptcies – in order to deconstruct the common idea of border failure in the Americas.